2016
DOI: 10.1002/for.2427
|View full text |Cite
|
Sign up to set email alerts
|

Forecast Combinations in a DSGE‐VAR Lab

Abstract: We explore the benefits of forecast combinations based on forecastencompassing tests compared to simple averages and to Bates-Granger combinations. We also consider a new combination method that fuses test-based and Bates-Granger weighting. For a realistic simulation design, we generate multivariate time-series samples from a macroeconomic DSGE-VAR model. Results generally support Bates-Granger over uniform weighting, whereas benefits of test-based weights depend on the sample size and on the prediction horizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…A few years later, Song et al [31] similarly stated that according to their results, forecast combination only improved forecasting performance in the tourism context in just over 50% of all cases compared with the most accurate single prediction. In a similar vein, Gunter and Önder [12] found that combined forecasts based on Bates-Granger weights, on multiple forecast encompassing tests, as well as on a combination of the two approaches [32]. The authors applied the aforementioned forecast combination techniques to Google Analytics indicators used as leading indicators for forecasting tourist arrivals to Vienna.…”
Section: Related Literaturementioning
confidence: 95%
“…A few years later, Song et al [31] similarly stated that according to their results, forecast combination only improved forecasting performance in the tourism context in just over 50% of all cases compared with the most accurate single prediction. In a similar vein, Gunter and Önder [12] found that combined forecasts based on Bates-Granger weights, on multiple forecast encompassing tests, as well as on a combination of the two approaches [32]. The authors applied the aforementioned forecast combination techniques to Google Analytics indicators used as leading indicators for forecasting tourist arrivals to Vienna.…”
Section: Related Literaturementioning
confidence: 95%
“…Gunter and O ¨nder (2016) and Shen et al (2011) used a multiple forecast that encompassed testing to determine the constituent models that remained to be combined. Uniform weights can be applied to these surviving models (Costantini et al, 2017). By contrast, the sum of weights is not always equal to one for nonlinear combination methods, which is necessary to identify the interactions among the relevant criteria.…”
Section: Forecast Combinationsmentioning
confidence: 99%
“…t is insignificant at a specific level of significance. As a result, encompassing tests eliminate uninformative rival models (Costantini et al, 2017).…”
Section: Forecast Encompassing Testmentioning
confidence: 99%